El Vedado / Havana (Cuba): consequences of the transformation process within a former upper-class residential quarter - Mertins, Günter; Sardiñas Gómez, Orestes (ERDKUNDE, 2014)
The investigation presented here pursued two targets. On the one hand, there is the documentation of the recent (2011) building condition and use of the buildings, supplemented by information about the building phases and the number of building storeys for the former classical upper-class district El Vedado in Havana/Cuba. It is considered one of the oldest (or even the oldest?) privately planned urban quarters in Latin America. On the other hand, there is the analysis of the transformation-reasons concerning the clearly different building conditions and the corresponding building uses. The article starts with brief sections about the development of El Vedado up to 1958 and its urban-geographical, historical and architectural position within the Latin American context.